Compound dry-hot-fire events connecting Central and Southeastern South America: an unapparent and deadly ripple effect - Djacinto Monteiro dos Santos; Aline M. de Oliveira; Ediclê S. F. Duarte; Julia A. Rodrigues; Lucas S. Menezes; Ronaldo Albuquerque; Fabio de O. Roque; Leonardo F. Peres; Judith J. Hoelzemann; Renata Libonati (npj Natural Hazards)
Abstract South America has experienced severe compound drought-heatwaves (CDHW), exacerbating fires. Recently, the unprecedented Pantanal 2020 fire season (P20F), burning a third of the biome, resulted in well-reported local impacts on the ecosystem, economy, and health. Nevertheless, the long-range ripple effects of this event remain unknown. We investigated the P20F-related cascading hazards, integrating models, observational and satellite-based data. P20F-related smoke elevated PM2.5 levels in the SA’s most populated area, exceeding WHO guidelines by up to 600%. Smoke-induced air pollution episodes coincided with widespread heatwaves, amplifying health risks. The mortality burden attributable to this multi-hazard short-term (14 days) exposure was estimated to be 2150 premature deaths (21% increase above expected levels). Our findings highlight that the impacts of CDHW-fires in SA are beyond the local level, implying growing challenges for risk management and public health and the need for governance based on telecoupled flows, linking different systems over multiple scales.